Modelling quantum software: an annotated bibliography - Bibbo, Luis Mariano (2024)
This annotated bibliography delves into the field of quantum computing, focusing specifically on the resources used throughout the software life cycle. It examines several published works that analyze quantum software modelling in the context of the various phases of the life cycle, from analysis/requirements to testing and maintenance. Each annotation provides an analysis of software engineering resources applicable to quantum software development and their applicability to different phases of the software development process. By synthesizing these diverse perspectives, this bibliography illuminates the evolving landscape of quantum software development and underscores the critical role of modelling in the context of software engineering. The result provides a valuable starting point for researchers and practitioners who wish to deepen the interplay between quantum computing and software engineering, fostering innovation and advances in this evolving field.